PENGGUNAAN PLATFORM PEMBELAJARAN DIGITAL BERBASIS GOOGLE SITES PADA MATERI BERKENALAN DENGAN BUMI KITA KELAS V SD NEGERI GUE GAJAH KAB.ACEH BESAR - Sauqi Aulia Hakim; Mislinawati; Suci Fitriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In classroom practice, students often struggle to understand the concepts of the lithosphere, hydrosphere, and atmosphere in the topic “Getting to Know Our Earth” due to limited media and suboptimal technological integration. Based on this issue, the study formulates two research problems: (1) how teachers and students engage in learning activities using Google Sites in IPAS lessons on “Getting to Know Our Earth”, and (2) how student learning outcomes are affected after using Google Sites–based media. This study aims to describe instructional activities and student learning outcomes through the use of the Google Sites digital platform. This research employs a descriptive qualitative design involving 20 fifth-grade students of SD Negeri Gue Gajah. Data were collected through activity observations and learning outcome tests. The findings show that Google Sites contributes positively to the learning process. Teacher activities fall into the “good” category, reflected in planning, material delivery, and integration of features such as text, images, videos, hyperlinks, and online worksheets. Student activities are also categorized as good, indicated by active engagement, digital literacy, discussion participation, and independent navigation of content. Student learning outcomes improved, with most learners achieving scores above the minimum KKTP of 75% and demonstrating better understanding of the lithosphere, hydrosphere, and atmosphere. The study concludes that Google Sites is an effective digital learning medium that enhances engagement and learning outcomes in the “Getting to Know Our Earth” IPAS topic.